2022
DOI: 10.1002/ange.202207537
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Electrocatalytic Oxygen Evolution Over Atomically Dispersed Synergistic Ni/Co Dual Sites

Abstract: Single‐atom catalysts (SACs) are being pursued as economical electrocatalysts. However, their low active‐site loading, poor interactions, and unclear catalytic mechanism call for significant advances. Herein, atomically dispersed Ni/Co dual sites anchored on nitrogen‐doped carbon (a‐NiCo/NC) hollow prisms are rationally designed and synthesized. Benefiting from the atomically dispersed dual‐metal sites and their synergistic interactions, the obtained a‐NiCo/NC sample exhibits superior electrocatalytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Besides, the N 1s spectrum also comprises pyridinic N (398.5 eV), pyrrolic N (400.9 eV), quaternary (401.6 eV), and oxidized (404.3 eV) N species, respectively. [29,44] together with two wide satellite peaks, which is in line with the reported valence of SACs. [45,46] Page 9 of 17 Energy Advances…”
Section: Chemicals and Materialssupporting
confidence: 90%
See 1 more Smart Citation
“…Besides, the N 1s spectrum also comprises pyridinic N (398.5 eV), pyrrolic N (400.9 eV), quaternary (401.6 eV), and oxidized (404.3 eV) N species, respectively. [29,44] together with two wide satellite peaks, which is in line with the reported valence of SACs. [45,46] Page 9 of 17 Energy Advances…”
Section: Chemicals and Materialssupporting
confidence: 90%
“…[23][24][25][26][27][28] For example, Pei et al rationally designed and prepared atomically dispersed Ni/Co dual sites anchored on N-doped carbon hollow prisms, which shows excellent electrocatalytic performance toward OER. [29] Sun et al successfully synthesized atomically dispersed N-coordinated Ni-Fe dual-metal sites with higher electrocatalytic activity than monometal doped catalysts. [30] Wu et al reported atomically dispersed Fe-Co dual metal sites (FeCo-NC) derived from Fe and Co co-doped ZIF-8, which showed excellent bifunctional catalytic activity for the ORR and OER.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be possible that the longer bond length of Fe–N/O allows O 2 to bind in a Yeager-type fashion and supports full reduction to water. Lastly, it is likely that the limited SAC exposure could be hindering ORR performance. , The low surface area and lack of porosity observed in all CS-X-E samples inevitably prevent a large portion of SACs from being exposed for catalysis, reducing the ORR performance. In this regard, future work is needed to optimize the porosity.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the increasingly serious problems of resource depletion and environmental degradation, the development and utilization of clean and renewable energy is imminent. 1–11 Notably, the electrocatalytic hydrogen evolution reaction (HER) with zero carbon emission characteristics is the key path to produce hydrogen energy. 12,13 Among them, noble metal-based catalysts (especially Pt) have shown excellent advantages in the HER due to their ultra-high intrinsic activity.…”
Section: Introductionmentioning
confidence: 99%